SWARNNADWIPA ABAD XIII-XIV MASEHI PENGGUNAAN ATAS SUMBER EMAS DI HULU BATANGHARI (SUMATRA BARAT) - Utomo, Bambang Budi (BRIN, 1994)
Geographically, the territory of the Old Malay Kingdom was located around the Batanghari River, which included Jambi and West Sumatra Provinces. Based on the identification of calendar elements obtained from paleography, short writings on gold plates at Gumpung Temple, short inscriptions on pipisan stones from Koto Kandis, short writings on Buddhist areas from Solok Sipin, and ceramic fragments showing dates from the 13-14 AD century. The dating of the site shows that in the Batanghari area in the past there was a shift in settlement. The older settlements are located in the downstream area of ​​Batanghari, while the younger ones are located in the upstream area of ​​Batanghari in the West Sumatra region. The reason for moving the capital was due to the threat of a new religion that was developing in Aceh, but it can be added that Adityawarman also intends to control the gold mines that are widely located in the Minangkabau region. In addition, access to the Malacca Strait, which is an economic traffic route, is getting closer.